Education around medication review and deprescribing: a survey of medical and pharmacy students' perspectives - Alan J. Poots; Barry Jubraj; Emily Ward; Amante Wycoco; Nina Barnett (SAGE Publishing, 2020)
Research into the practice of medication review is developing across the world in response to the ever-increasing burden of inappropriate polypharmacy. Education, training and support of undergraduates and novice practitioners to equip them to participate in the medication review process could lead to long-term shifts in practice. The purpose of this study was to explore the awareness of pharmacy and medical undergraduates about medication review, deprescribing and polypharmacy, in order to inform improvement strategies. In November 2016, all final-year medical and pharmacy students at a London (UK) university were invited to complete a short questionnaire survey. Qualitative analysis inductively themed free-text comments and quantitative analysis used descriptive statistics to summarize responses, with chi-square tests used to indicate differences between the groups. The overall response rate was 34% (171/500). The terms 'medication review' and 'polypharmacy' were known to the students, whilst the term 'deprescribing' was unfamiliar with no difference between the groups. The term 'medication review' meant different things to the groups: pharmacy students suggested a focus on adherence and patient understanding, whilst medical students focused on interactions and whether medicines were still indicated. The groups differed in their perceptions of who they thought undertook reviews, who identifies potentially inappropriate medicines, who makes the final decision to deprescribe and the frequency of medication reviews. Both groups reported that on qualification they would not be comfortable stopping a medicine without discussion with a senior colleague, but would be comfortable prompting a senior colleague to review. Both groups had some awareness of medication review tools. The meaning of the term 'medication review' differed between the student groups. While medical students focused on clinical aspects, pharmacy students emphasized patient experience. Both groups anticipated a lack of confidence in deprescribing without senior support, highlighting the need for alignment between education and professional development syllabi in a way that combines the variety of professional perspectives. Prompts by juniors could lead to more medication reviews within existing practice, and may give them invaluable experience in reviewing medicines in their future careers as seniors.